Genetic Engineering of Mesenchymal Stem Cells - Nolta, Jan A.; Nolta, Jan A. (Springer Netherlands : Imprint: Springer, 2006)
MSC (mesenchymal stem cells) have been reported to initiate revascularization after injury, to facilitate engraftment of blood-forming stem cells, and to reduce the incidence of graft-vs. host disease through their immune-suppressive qualities. Finally, bone marrow-derived MSC have been reported to home to areas of solid tumor revascularization, and thus may be used as delivery vehicles to target ablative agents into dividing tumor cells. Recently the characteristics of human MSC from adipose (fat) tissue have also been identified. The possibility of repairing tissues, speeding stem cell engraftment, and targeting solid tumors for specific killing, using MSC easily harvested from bone marrow, or better yet, from unwanted fat tissue, holds broad appeal, and is an intriguing possibility that could have dramatic effect on health care. This book has information on how to isolate, grow, and characterize MSC from marrow and fat, and gives important insight into how these cells may be used for gene delivery and cellular therapies in the future. Updates on emerging clinical trials are given.